APPLYING INPUT OUPUT METHOD TO ANALYZE ESSENTIAL OILâS SUPPLY CHAIN (CASE STUDY: ESSENTIAL OF VETIVER OILâS SME IN GARUT) - Arsiyelis, Yulia
The elements of supply chain model are the initial supplier, a supplier, a manufacturer, a customer, and the final customer. There are several methods to build supply chain model. By using input output method can build the supply chain model compare with another methods or techniques. The objective of this research is to develop a model of Essential Oil’s Supply Chain using input output method. The model is used to analyze the Backward Linkages and Forward Linkages which consists of farmers, producers, suppliers, and distributors of essential oil’s SME. The solution of the model will be interpreted and used as the basis for policy formulation. A simulation was executed by combining farmers and manufacturers activities based on the result of model analysis. This simulation gives a positive result and indicated by the shift of farmers and manufacturers position from kuadran III to kuadran II. This also indicate that the industrial policy to develop essentials oil’s SME could be suggested. Based on the simulation, the policy has been proposed, namely improvement of human resource and research, development of applied technology, giving subsidize to farmers and manufacturers and also giving suggestion to plantation department for crossing plant policy to keep continuity raw material’s essential oil